The Russians are coming! The Russians are coming! : pageantry and patriotism in Cold-War America - Fried, Richard M., 1941- (Oxford University Press, 1998)
This book explores a widely lived yet little remembered facet of America's cultural and political history: the Cold War as experienced at the grassroots level. Here, Fried traces the cresting of modern patriotic observance during World War II and then shows how patriotic and civic activists afterwards labored to recreate a remembered unity and commitment in the tension-filled Cold War era. A variety of national and local entities mounted campaigns "to sell America to the Americans" through "rededication" celebrations like Know Your America Week and Freedom Week. The America